Pengaruh Supervisi Kepala Sekolah Terhadap Penerapan Metode Pembelajaran Pemberian Tugas Oleh Guru - Setiani Setiani (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The implementation of this class action departs from the background of the need for renewal in teaching and learning activities both carried out by teachers and by students in particular. Thus classroom action research plays an important role in improving the quality of learning activities so that teachers always make innovations or updates both on planning, implementing, evaluating, and analyzing learning activities. This study aims to the Effect of Principal Supervision on the Implementation of Teaching Methods of Giving Assignments by Teachers in Improving Student Achievement at SDN 016503 Tanah Rakyat Kec. Pulo Bandring TP. 2019/2020. The school action research was conducted at SDN 016503 Tanah Rakyat Kec. Pulo Bandring. The subjects of this study were teachers of SDN 016503 Tanah Rakyat Kec. Pulo Bandring, observation data, interviews, tests, and documentation studies. This school action research was carried out in 2 cycles, each cycle consisting of planning, acting, observing and reflecting. Keywords: assignment; headmaster; learning achievement; supervision; teacher Abstrak: Dilaksanakannya penelitian tindakan kelas ini berangkat dari latar belakang perlunya pembaruan dalam kegiatan belajar mengajar baik yang dilakukan oleh guru maupun oleh siswa khususnya. Dengan demikian penelitian tindakan kelas sangat berperanan penting dalam meningkatkan mutu kegiatan pembelajaran agar guru selalu mengadakan inovasi atau pembaharuan baik terhadap perencanaan, pelaksanaan, evaluasi, maupun menganalisis kegiatan pembelajaran. Penelitian ini bertujuan untuk Pengaruh Supervisi Kepala Sekolah Terhadap Penerapan Metode Pembelajaran Pemberian Tugas Oleh Guru Dalam Meningkatkan Prestasi Belajar Siswa di SDN 016503 Tanah Rakyat Kec. Pulo Bandring TP. 2019/2020. Penelitian tindakan sekolah dilaksanakan di SDN 016503 Tanah Rakyat Kec. Pulo Bandring. Subjek penelitian ini adalah guru SDN 016503 Tanah Rakyat Kec. Pulo Bandring, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Penelitian tindakan Sekolah ini dilaksanakan dalam 2 siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Kata Kunci: guru; kepala sekolah; pemberian tugas; prestasi belajar; supervise